Analisis Kesulitan Belajar Siswa Pada Mata Pelajaran Matematika Sekolah Dasar - Maya Anggraini; Syahrial Syahrial; Urip Sulistiyo (Peneliti.net, 2020)
Based on the results of preliminary observations in grade IV of elementary school, it shows that there are students who are slow in doing assignments during the mathematics learning process, both from taking notes and answering written questions from the teacher so that it can be said that there are obstacles in the learning process. In addition, the researcher also found that during the learning process using groups, the researcher also saw that these students were alienated by their friends so that no friends wanted a group with them, this was part of the student's learning problem. The research was conducted using qualitative descriptive research methods. Which was held in January 2020. And the informants of the research were students of class IVA SDN 73 / IX Simpang Sungai Duren. Data collection was carried out by observation and interviews. The results of data analysis indicate that the characteristics of student learning difficulties in mathematics can be seen in the problem of indifferent attitudes in the mathematics learning process. This learning difficulty occurs from internal factors, namely the absence of an action or action in learning and a lack of self-confidence when carrying out or being involved in an activity.Furthermore, the causes of external factors are seen from family factors, where the economic condition of the family is below the average. parents to be more active in earning a living so that it affects the child's lack of attention in guiding and teaching learning at home.